Hypolipidemic activity of Ipomoea aquatica Forsk. Leaf extracts on lipid profile in hyperlipidemic rats. - Sivaraman, Dhanasekaran (International Journal of Pharmaceutical & Biological Archive, 2010)
The study aimed at evaluating the hypolipidemic effects of Ipomoea aquatica Forsk (MEIA) and investigating the potential mechanisms by which MEIA modulated lipid profiles in hyperlipidemic rats. Hypolipidemic effects of the single, daily oral dosing of 200 and 400 mg/kg of methanol leaf extract of Ipomoea aquatica Forsk (MEIA) in Swiss albino rats for 30 days. On day 30, blood samples from the rats were collected for the estimation of total cholesterol, total lipid, free fatty acid, phospholipids, and triglycerides. The concentrations of plasma total cholesterol, total lipid, free fatty acid, phospholipid, and triglycerides in rats treated with MEIA at 200 and 400mg /kg were significantly decreased (P < 0.05), accompanied with significantly decreased concentrations of liver, kidney and heart total cholesterol and triglyceride (P < 0.05). These results indicated that MEIA largely improved the lipid profiles in the hyperlipidemic rats <!--[if !supportEmptyParas]--> <!--[endif]-->